Well-differentiated liposarcoma of the hypopharynx: Two case reports and literature review. Issue 3 (2019) - Köping, Maria; Hagen, Rudolf; Michael, Schneider; Beck, Christopher; Grunz, Jan-Peter; Scherzad, Agmal
No abstract available